Ketertarikan dan Kesukaan Kecoak Jerman, Blatella germanica L. (Dictyoptera: Blattellidae) Terhadap Fagostimulan Berbeda - Femilia Hajar Ilhami; Trisnowati Budi Ambarningrum; Hery Pratiknyo (BioEksakta : Jurnal Ilmiah Biologi Unsoed, 2020)
German cockroaches (Blatella germanica) L. are includes in settlement bugs that are hard to terminate. One alternative to control German cockroaches that are using bait. To make bait formulation, the first thing is look for the type of phagostimulant that can be interesting and attractive to German cockroaches. The purpose of this research is to study the type of phagostimulant that has the ability to attract and liked by German cockroaches. Phagostimulant types used are bananas, durian, sugar formulations, and erythrisol. Data from observations of interest in test interest were analyzed using the t test and calculation of the attraction index, while the data for German roaches favored were analyzed using ANOVA and index feeding calculations. The results obtained were that German cockroaches were attracted to bananas, durian, sugar formulations, and erythrisol. ANOVA analysis results obtained sig 0.029 (p <0.05). The results of the calculation of the attractiveness index and feeding index obtained German cockroaches are preferred by bananas compared to other phagostimulants. The conclusion of this study is the type of phagostimulant that can attract cockroaches Germany is banana, durian, sugar formulation, and erythrisol, while the type of phagostimulant most preferred by German cockroaches is banana.